The Influence of Electronic Word of Mouth, Service Quality, and Cafe Atmosphere on Purchasing Decisions at Zozo Garden Coffeeshop - Ningsih, Rima; Rinova, Dora (Journal of Environmental Economics and Sustainability, 2025)
This research investigates how Electronic Word of Mouth, Service Quality, and Café Atmosphere influence purchasing decisions at Zozo Garden Coffeeshop in Bandar Lampung City. A quantitative approach with descriptive methods was employed, utilizing purposive sampling to select a sample of 96 respondents. Multiple linear regression analysis was used to process the data. Results from the t-test indicate that Electronic Word of Mouth significantly impacts purchasing decisions at Zozo Garden Coffeeshop. Likewise, Service Quality and Café Atmosphere also significantly affect purchasing decisions. The R Square value of 0.708 from the coefficient of determination test suggests that these three variables explain 70.8% of purchasing decisions, with the remaining 29.2% attributable to other factors outside the study's scope.